Flourishing together: research protocol for developing methods to better include disabled people's knowledge in health policy development - Rachelle A. Martin; Angelo P. Baker; Kirsten Smiler; Lesley Middleton; Jean Hay-Smith; Nicola Kayes; Catherine Grace; Te Ao Marama Apiata; Joanne L. Nunnerley; Anna E. Brown (BMC, 2022)
Abstract Background To positively impact the social determinants of health, disabled people need to contribute to policy planning and programme development. However, they report barriers to engaging meaningfully in consultation processes. Additionally, their recommendations may not be articulated in ways that policy planners can readily use. This gap contributes to health outcome inequities. Participatory co-production methods have the potential to improve policy responsiveness. This research will use innovative methods to generate tools for co-producing knowledge in health-related policy areas, empowering disabled people to articulate experience, expertise and insights promoting equitable health policy and programme development within Aotearoa New Zealand. To develop these methods, as an exemplar, we will partner with both tāngata whaikaha Māori and disabled people to co-produce policy recommendations around housing and home (kāinga)-developing a nuanced understanding of the contexts in which disabled people can access and maintain kāinga meeting their needs and aspirations. Methods Participatory co-production methods with disabled people, embedded within a realist methodological approach, will develop theories on how best to co-produce and effectively articulate knowledge to address equitable health-related policy and programme development-considering what works for whom under what conditions. Theory-building workshops (Phase 1) and qualitative surveys (Phase 2) will explore contexts and resources (i.e., at individual, social and environmental levels) supporting them to access and maintain kāinga that best meets their needs and aspirations. In Phase 3, a realist review with embedded co-production workshops will synthesise evidence and co-produce knowledge from published literature and non-published reports. Finally, in Phase 4, co-produced knowledge from all phases will be synthesised to develop two key research outputs: housing policy recommendations and innovative co-production methods and tools empowering disabled people to create, synthesise and articulate knowledge to planners of health-related policy. Discussion This research will develop participatory co-production methods and tools to support future creation, synthesis and articulation of the knowledge and experiences of disabled people, contributing to policies that positively impact their social determinants of health.